DISCOURSE ANALYSIS OF THE SARA MILLS MODEL OF THE RELIGIOUS ANIMATED FILM BY CISFORM UIN SUNAN KALIJAGA WITH THE TITLE "MOSQUE FOR ALL" - Muhammad Anshori; Ali Ridho (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The development of films today is unstoppable, because as a means of entertainment and information as in the animated film "Masjid Untuk Semua" by CISform UIN Sunan Kalijaga which succeeded in coloring Indonesian animated films with content not only entertainment but knowledge information with Islamic nuances (Religion). In the animated film "Masjid Untuk Semua" tells the story of a non-Muslim entering the mosque so that there is a debate that infidels are prohibited from entering the mosque. But with the interest of research, it is allowed as the Prophet Muhammad SAW also did not prohibit Abu Sofyan before. With Sara Mills' discourse analysis based on her theoretical framework. This movie tells the role of men and women as subjects (storytellers) and religion as objects (those told). Where men and women do not marginalize the position of others who are not in the same Islamic faith. The role of the dominant character so that the message of the mosque for all can be conveyed to the audience. In this film, the author also analyzes that there is a great interest in this film, namely to change the paradigm that mosques for all have no religious distinctions, intentions with good intentions.